One million rounds fired in 12 hours? An analysis of the account of six guns of the 100th Brigade Machine Gun Company at High Wood in August 1916 - Fisher, Richard; Willis, Richard (Taylor & Francis, 2019)
The Great War saw machine gunnery develop from a direct fire weapon through to mass indirect fire barrages. There is an account from High Wood in August 1916 that represents the pinnacle of these developments – firing one million rounds from ten guns in 12 hours. This research examines that account to determine what happened and the technical and logistical requirements of such a feat. By examining the war diaries and characteristics of the Vickers machine gun, it has been possible to identify what actually took place, what would have been necessary for one million rounds to be fired and the potential of Great War machine gunnery.
Keywords: Machine gun; small arms; weaponry; tactics; logistics